Evolution of land cover from 1989 to 2023 in the southern region of the Ñeembucú department, Paraguay - Vera, Porfírio Domingo Arévalos; Pereira, Walter Esfrain (Revista JRG de Estudos Acadêmicos, 2024)
This research study, conducted in the southern region of the Ñeembucú Department, Republic of Paraguay, aims to investigate the evolution of land cover from 1989 to 2023. The study area encompasses the districts of Pilar, Humaitá, Paso de Patria, General Díaz, Mayor Martínez, Isla Umbú, Desmochados, Guazu Cuá, Tacuaras, Villalbín, and Laureles. The research was initiated due to concerns regarding the degradation of wetlands, especially since this region is considered unique in the country. In recent years, the southern region of the Ñeembucú Department has undergone numerous human interventions, primarily for productive purposes. The study area, covering a total surface of 6,636.5 km², was demarcated. Subsequently, LANDSAT satellite images were obtained through the U.S. Geological Survey, selected for less than 20% cloud cover. The selected area was then delineated by cropping the images to the specified extent using QGIS 3.32 software and the Semi-Automatic Classification plugin, facilitating the semi-automatic classification of land cover. Significant deforestation, an increase in areas without land cover, urban areas, and sparse vegetation, as well as a decrease in the extent of swamps, forests, grasslands, and prairies were observed.